2018
DOI: 10.1007/s10198-018-1012-0
|View full text |Cite
|
Sign up to set email alerts
|

Including intangible costs into the cost-of-illness approach: a method refinement illustrated based on the PM2.5 economic burden in China

Abstract: The concentrations of particulate matter with aerodynamic diameters less than 2.5 µm (PM 2.5 ) and 10 µm (PM 10 ) is a widespread concern and has been demonstrated for 103 countries. During the past few years, the exposure-response function (ERf) has been widely used to estimate the health effects of air pollution. However, past studies are either based on the costof-illness or the willingness-to-pay approach, and therefore, either do not cover intangible costs or costs due to the absence of work. To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Beyond direct health care cost, indirect costs also have a significant contribution to the total cost of illness [27]. Studies published since 2010 have reported that cGVHD burden of illness translates into a higher cost to society and loss of productivity from those patients with cGVHD who are unable to work [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond direct health care cost, indirect costs also have a significant contribution to the total cost of illness [27]. Studies published since 2010 have reported that cGVHD burden of illness translates into a higher cost to society and loss of productivity from those patients with cGVHD who are unable to work [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a lack of European data on indirect costs, with the majority of data from North America [16,28,29]. Considering direct healthcare costs in parallel with the indirect cost [27] is important to provide a more integrated insight into the economic burden of cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…The ensuing phenomenon will appear in the atmospheric precipitation of inland cities, and the composition of sea salt ions is higher than that of coastal cities. Of course, the final conclusion needs further observation, analysis and verification [48][49][50][51][52][53][54][55][56][57][58].…”
Section: Variation Characteristics Of Precipitation Ion Compositionmentioning
confidence: 98%
“…Compared with other optimization algorithms, the GOA possesses the advantages of an uncomplicated structure, few control parameters, and simple implementation. There are many fields such as engineering optimization, image processing [43], multi fault condition monitoring [44], data science [45], air pollution concerns [46], and data clustering that can be solved by using an optimization process based on GOA. Many scholars worldwide have carried out many studies and improvements from multiple angles to cope with low speed, low-precision solutions, and quickly fall into local optima [47].…”
Section: Introductionmentioning
confidence: 99%